2009
DOI: 10.1093/annonc/mdn602
|View full text |Cite
|
Sign up to set email alerts
|

Trends in quality of end-of-life care for Taiwanese cancer patients who died in 2000–2006

Abstract: The quality of end-of-life care for Taiwanese cancer decedents was substantially inferior to that previously reported and to that recommended as benchmarks for not providing overly aggressive care near the end of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 36 publications
7
102
4
Order By: Relevance
“…The importance of such research is evident, as disparities between countries, within countries and among different patient populations do matter on many levels such as quality of care issues [26,27,28,29,30,31], economical aspects [32,33,34] or shifts in the delivery of care over time [35]. …”
Section: Discussionmentioning
confidence: 99%
“…The importance of such research is evident, as disparities between countries, within countries and among different patient populations do matter on many levels such as quality of care issues [26,27,28,29,30,31], economical aspects [32,33,34] or shifts in the delivery of care over time [35]. …”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, of all those receiving hospice care, 12.4 % receive it at home while 87.6 % receive it in the hospital. Still the overall use of either hospital-and homebased hospice services in Taiwan by those during their last year of life has only gradually increased for over the last 20 years, and it remains underutilized at 7.34 % in 2000 and 16.83 % in 2006 [1]. This underutilization has also been reported in the USA [2].…”
Section: Introductionmentioning
confidence: 99%
“…ED may be the choice for immediate relief of symptoms for the majority of cancer patients. A recent retrospective study on quality of end-of-life care for Taiwanese cancer patients reported that 16-21% of cancer patients in their last month of life visited the ER more than once [15].…”
Section: Introductionmentioning
confidence: 99%